SIMULATION PROGRAMS IN DISTANCE LEARNING - Ptak, Paweł (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In the era of the development of computer technology, methods were created that enable teaching, not only through direct contact with the student, but also through the computer network and the Internet. In order for this to be possible, programs allowing this type of activity had to be created. They are to model the operating conditions of electronic and measurement systems in virtual space as much as possible. Such programs must reflect the operation of such systems under operating conditions, taking into account disturbing signals. They should also be adapted to remote work via the Internet. In the era of epidemics, when the possibilities of teaching in the classical form are very limited or impossible, simulation programs working in a network environment may make sense. The results of modeling the operation of systems in virtual reality and the created measurement systems can be sent electronically. This allows their verification with the laboratory teacher and joint work on the project by a group of students during the laboratory classes.